SURGICAL TREATMENT OF PEDIATRIC UROLITHIASIS - Đokić, Milena; Đokić, Ana; Dobrodolac, Milica; Ilić, Predrag (Medicinski podmladak, 2022)
Introduction: Surgical treatment of urolithiasis in children is quite complex and specific due to certain anatomical and functional features of childhood. Methods of surgical treatment at this age are: extracorporeal lithotripsy (ESWL), intracorporeal (endoscopic) lithotripsy: pneumatic and laser, percutaneous nephrolithotripsy (PCNL) and open surgery.  The aim of this study was evaluation of the effects of ureterorenoscopy and endoscopic lithotripsy in children, as methods of minimally invasive surgical treatment.Material and methods: The retrospective study was conducted at the Mother and Child Health Care Institute of Serbia "Dr Vukan Cupic" in Belgrade from 2010 to 2020. The study included 112 patients (50 boys and 62 girls) aged 1-18 years with urolithiasis, treated by endoscopic (laser or pneumatic) lithotripsy. Results: After one ureterorenoscopy, the calculus was successfully disintegrated in 87 (78%) patients: in the renal pelvis in 22 (79%), in the upper pole calices of the kidney in 14 (100%), in the lower pole calices in 10 (50%), in the proximal segment of the ureter in 10 (83%), in the distal segment of the ureter in 27 (79%), in the bladder in 4 (100%) cases. In 19 (17%) patients the second intervention was necessary: in the renal pelvis in 28 (100%), in the upper pole calices in 14 (100%), in the lower pole calices in 14 (70%),  in the proximal segment of the ureter in 12 (100%), in the distal segment of the ureter in 34 (100%) and in the bladder in 4 (100%) patients.Conclusion: The primary treatment of pediatric urolithiasis is ureterorenoscopy in combination with pneumatic or laser lithotripsy. It is successfully used in all segments of the urinary tract. The procedure is partially limited in the lower pole calices of the kidney, due to anatomical circumstances and mechanical limitations of the instruments.Key words: urolithiasis, children, lithotripsy, ureterorenoscopy, efficacy
Keywords: urolithiasis, children, lithotripsy, ureterorenoscopy, efficacy